MEKANISME PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL MELALUI DISPUTE SETTLEMENT BODY (DSB) WORLD TRADE ORGANIZATION (WTO) (TINJAUAN TERHADAP GUGATAN INDONESIA KEPADA KOREA SELATAN DALAM PENGENAAN BEA MASUK ANTI-DUMPING PRODUK KERTAS) - Ratnasari, Diah; Sukihana, Ida Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This writing shall be entitled as “Mechanism of Trade Dispute Settlement through World Trade Organization (WTO) Dispute Settlement Body (DSB) (Analysis towards Indonesia vs South Korea on Income Tarrif of Anti-dumping for Paper-related Product Case)”. This writing shall apply normative legal research method combined with several approaches of regulatory, casuistic, and factual approach respectively. This writing shall illustrate the chronological order of dispute settlement sequences of the related case between Indonesia and South Korea. Conclusion drawn from this writing shall be illustrating the mechanism initiated by bilateral consultation which shall be proceeded with the establishment of WTO DSB Panel which further recommended that the South Korea to conduct a review regarding Anti-Dumping Agreement (ADA) provision of Indonesian paper-related product.
Keywords: Mechanism, Dispute Settlement Body, WTO, Anti-dumping